Four new records of myxomycetes from China - Song, Wen-Long; Lin, Di; Li, Min; Du, Que; Chen, Shuang-Lin (Phytotaxa, 2022)
Four species of myxomycetes are reported from China for the first time. Cornuvia serpula and Perichaena microspora were discovered from Houhe Nature Reserve in Hubei Province. Criterium muscorum and Diderma fragile were discovered from Yaoluoping Nature Reserve in Anhui Province. Their morphological features are described and illustrated by light microscope and scanning electron microscope. These specimens are deposited in Herbarium of Fungi of Nanjing Normal University (HFNNU).